Dynamics of Liquid Solidification Thermal Resistance of Contact Layer - Lipnicki, Zygmunt; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This monograph comprehensively describes phenomena of heat flow during phase change as well as the dynamics of liquid solidification, i.e. the development of a solidified layer. The book provides the reader with basic knowledge for practical designs, as well as with equations which describe processes of energy transformation. The target audience primarily comprises researchers and experts in the field of heat flow, but the book may also be beneficial for both practicing engineers and graduate students.
Introduction -- Solidification -- Solidification of PCM Materials -- The Model of Solidification of A Liquid with the Contact Layer -- Solidification on a Rectangular Geometrics -- Solidification in an Annular Space -- Solidification of a Liquid Flowing into the Channel -- The Role of the Contact Layer in a Solidification Process -- Phase Heat Accumulator.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Mathematics -- Data processing; Mathematical physics; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Computational Science and Engineering; Mathematical Methods in Physics